An exploration of why men with severe haemophilia might not want gene therapy: The exigency study. Issue 5 (15th July 2021) - Fletcher, Simon; Jenner, Kathryn; Holland, Michael; Chaplin, Steve; Khair, Kate
Abstract: Introduction: For many people with haemophilia (PwH) gene therapy offers a potential functional cure. However, some have stated that they do not wish to have gene therapy either now or in the future. Aim: This sub‐study, part of the larger Exigency programme, assesses the attitudes, views and understanding of those who do not wish to undergo gene therapy. Methods: Participants were approached via social media and word of mouth referral and invited to participate in a focus group or individual interview to discuss their views. Interviews were recorded, transcribed verbatim and analysed thematically. Results: Ten adult men with severe haemophilia (eight haemophilia A and two haemophilia B), mean age 34.3 years, participated in a 1‐h focus group (n = 9) or interview (n = 1). All were on prophylaxis. None reported significant treatment burden, and all had annual bleeding rates of less than five in the previous 12 months. Four major themes emerged: self‐identity and its loss, lack of long‐term safety and efficacy data, ongoing concerns about past viral infection, and lack of current treatment burden. Conclusion: There are many concerns about gene therapy, including eligibility, effectiveness and safety, which may result in individuals declining it as a therapy. These concerns may recede as more data are published. This study reveals a psychological dynamic around self‐identity and belonging for PwH. The nature of this dynamic is poorly understood and needs exploration to facilitate support for those making decisions about gene therapy.